Analysis of design thinking models and identifying their role and dimensions: A systematic review - Zahrā Abolhasani; Marziye Dehghāni; Mohammad Javādipour; Keyvān Sālehi; Nasrin Mohammadhasani (فصلنامه نوآوری‌های آموزشی, 2021)
Design thinking is a participatory problem-solving approach with a human-centered approach that enhances innovation by increasing learners' creative thinking abilities. The purpose of this study was to analyze the concept of design thinking and reviewing the models of design thinking by collecting, evaluating and systematically reviewing articles related to this topic. In this study, the databases of ERIC, Science Direct, Tyler & Francis, and Springer were searched, and all English articles indexed in their databases from 2000 to 2020 were collected. After searching the databases, the relevant articles were selected and evaluated according to the CASP evaluation criterion, and finally 36 articles were analyzed. The selected studies were divided in three groups: 1- articles that have provided a new definition of design thinking. 2- those which have presented new models. 3- those which used models in the implementation of the plan; and then they were evaluated.